Kekuatan Pembuktian Surat Pengakuan yang Dibuat di Hadapan Kepala Desa/Lurah sebagai Bukti Kepemilikan Hak Atas Tanah (Studi Kasus: Putusan Pengadilan Negeri Balige Nomor 101/Pdt.G/2020/PN.Blg) - Elvira, Lily (Universitas Ekasakti, 2023)
Land problems arising from land rights that do not have legal certainty, including issues regarding Letters of Recognition of land rights that have not been registered into a certificate still occur in the community today. This results in the emergence of control over land parcels by parties that are not in accordance with the provisions of laws and regulations, such as claiming a piece of land by someone who is not necessarily entitled to the land concerned. This study raises the issue of the evidentiary power of a letter of recognition as a means of proof of ownership of land rights. The method used is research in the form of normative juridical, with a research approach, namely a legal approach and a case approach. The source of data used as material for completeness of data is secondary data by means of data collection, namely document studies. The results of this study explain that before the enactment of the UUPA, a Letter of Recognition of land rights made before the Head of the Village / Lurah or local sub-district head was still recognized as proof of ownership of land rights. However, after the enactment of the provisions of the UUPA, PP 24/1997, and PP 18/2021, written evidence of customary land other than certificates cannot be used as evidence of ownership of land rights and is only a guide in the land registration process.